Online Game Addiction in Adolescents - Lona, Andhiny Febryani; Aipipidely, Diana; Anakaka, Dian Lestari (Universitas Nusa Cendana, 2023)
Online gaming addiction is a disorder caused by excessive gaming habits. Addiction can harm a person's psychological health. Addicted online gamers can do negative things, such as being aggressive, saying dirty or rude words, abandoning important activities, and changing in eating and sleeping patterns. Someone who is addicted to online games ultimately does not care about the surrounding environment because they tend to be absorbed in their world. This study aims to determine the description of online game addiction in adolescents at SMK Negeri 1 Kupang. This type of research is descriptive quantitative. Respondents in this study were 241 students aged 15-18 years old. The results of the data analysis showed that 51% of students experienced addiction.